A numerical algorithm for the optimal placement of inset maps - Varsamis, Dimitris; Papakonstantinou, Apostolos (My University, 2016)
The purpose of this paper is to present an algorithmic formulation addressing the cartographic problem of siting an inset map at specific map locations under spatial and cartographic constraints. The first part of the paper aims at: (a) presenting a numerical algorithm that solves the above siting problem under such constraints, and (b) investigating the effectiveness of this numerical algorithm for a more general geo- graphical problem, that of siting an anthropogenic structure or object of rectangular shape in suitable areas. The second part of this paper showcases the computational implementation of the above algorithm for addressing the cartographic problem of inset map placement in areas with land discontinuity.
Keywords: Numerical algorithm; Inset map placement; Complexity